2006
DOI: 10.1021/la0535126
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Azimuthal Anchoring Energy of Liquid Crystals in Contact with Oligo(ethylene glycol)-Terminated Self-Assembled Monolayers Supported on Obliquely Deposited Gold Films

Abstract: We report measurements of the orientations and azimuthal anchoring energies of the nematic liquid crystal 4-cyano-4'-pentylbiphenyl (5CB) on polycrystalline gold films that are deposited from a vapor at an oblique angle of incidence and subsequently decorated with organized monolayers of oligomers of ethylene glycol. Whereas the gold films covered with monolayers presenting tetra(ethylene glycol) (EG4) lead to orientations of 5CB that are perpendicular to the plane of incidence of the gold, monolayers presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(83 citation statements)
references
References 50 publications
2
81
0
Order By: Relevance
“…31,32 Single component monolayers of EG4 are known to orient nematic 5CB with an easy axis that is perpendicular to the in-plane direction of gold deposition, evident in Figure 5 (top squares) as a twist angle of 87.9 ° ± 1.0 °. 13 The orientation of the 5CB on the EG4 monolayer deviated from the orientation of the easy axis by an angle of φ = 0.2 ° ± 1.2 °, which indicates that the monolayer of EG4 caused strong anchoring of 5CB. A previous study concluded that SAMs of EG4 formed from aqueous solutions are more ordered than SAMs of EG4 deposited from ethanolic solutions.…”
Section: Imaging Of Competitive Co-adsorption Of Mixtures Of Organothmentioning
confidence: 93%
See 1 more Smart Citation
“…31,32 Single component monolayers of EG4 are known to orient nematic 5CB with an easy axis that is perpendicular to the in-plane direction of gold deposition, evident in Figure 5 (top squares) as a twist angle of 87.9 ° ± 1.0 °. 13 The orientation of the 5CB on the EG4 monolayer deviated from the orientation of the easy axis by an angle of φ = 0.2 ° ± 1.2 °, which indicates that the monolayer of EG4 caused strong anchoring of 5CB. A previous study concluded that SAMs of EG4 formed from aqueous solutions are more ordered than SAMs of EG4 deposited from ethanolic solutions.…”
Section: Imaging Of Competitive Co-adsorption Of Mixtures Of Organothmentioning
confidence: 93%
“…[12][13][14] In this approach, a nematic LC such as 4'-pentyl-4-cyanobiphenyl (5CB, Figure 1A) is confined between two surfaces that are structured so as to promote the LC to adopt mutually orthogonal orientations at the two confining surfaces ( Figure 1B). The interactions of the LC with the two confining surfaces cause a twist distortion to form within the LC.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38] In addition to the surfactant studies described above, the optical response triggered by surface anchoring changes of LC systems has been used to investigate many different surface processes. These include the patterning of solid surfaces, [1,4,6,9,14,23,24] surface re-organisation of adsorbed phospholipids, [12,20] protein and ligand binding, [2,5,8,10,16,17,18,22,21] bound virus imaging, [15] chemical [3] and enzyme catalysed reactions, [13] the pH response of adsorbed polymers, [26] layer-by-layer polymer film assembly [25] and DNA hybridisation. [28] Herein we show that the planar-homeotropic transition can be induced by the adsorption of various UV polymerisable surfactants and that, in some cases, UV polymerisation of the adsorbed film triggers a homeotropic-planar transition.…”
Section: Introductionmentioning
confidence: 99%
“…This result contrasts to all past studies of ω-terminated alkanethiols on gold films in which the easy axes of smectic and nematic LCs have been measured to be either parallel or perpendicular to the direction of deposition of the gold film. 18,19,27,31,38,62,63 This point, which is related to the chirality of the adsorbates, is addressed in detail in the Discussion. Third, we note that there is a substantial difference between the orientations assumed by nematic 5CB on the gold films decorated with either L-C-L-Y or L-C-L-[p]Y.…”
Section: Resultsmentioning
confidence: 97%
“…25,38 Semitransparent gold films (used for optical measurements of LC orientations) were prepared by sequentially depositing 8 nm of Ti and 20 nm of Au. The films were deposited at an angle of incidence of 35° ± 1°.…”
Section: Methodsmentioning
confidence: 99%